Research progress on Traditional Chinese Medicine treatment and nursing interventions for drug-induced phlebitis (药物性静脉炎的中医药治疗和护理干预研究进展) - XIN Jiayun (忻嘉芸); WANG Yanping (王燕萍) (Journal of International Translational Medicine Limited, 2024)
Drug-induced phlebitis not only increases the pain and economic burden of patients, but also influences the course of treatment. Traditional Chinese medicine is widely used in clinical practice, and it has unique advantages in the treatment of drug-induced phlebitis. By reviewing relevant studies from perspectives of the causes of drug-induced phlebitis, the treatment methods of Traditional Chinese medicine and nursing interventions, this paper aims to provide new ideas for the clinical solution of drug-induced phlebitis and help nursing staff to improve nursing safety and drug awareness, so that they can use traditional Chinese medicine to treat pharmaceutical phlebitis more reasonably. (药物性静脉炎不仅增加患者痛苦和经济负担, 同时也不利于疾病的治疗。中医药在临床应用广泛, 其在治疗药物性静脉炎方面有着独特的优势。本文就药物性静脉炎发生原因、中医药治疗方法和护理干预进行综述, 旨在为临床治疗药物性静脉炎提供新思路和帮助护理人员提高护理安全和用药意识。)